Identifying and debunking environmental-related false news stories – An experimental study - Sven Grüner (ZBW - Leibniz Information Centre for Economics, 2020)
Informed decisions are the cornerstone of a functioning democracy. The goal of this paper is twofold. First, to explore who is good at distinguishing between true and false, and, second, to learn something about mechanisms to debunk false news stories. In an experimental study, subjects were shown several news studies and asked to rate them as true or false. After this exercise, the subjects received systematically varied information about the correctness of the news stories depending on the experimental condition they had been assigned to. After a delay of three weeks, the subjects were shown the news studies again to find out which one works best. Our main findings are (i) The perceived familiarity with news stories increases the propensity to accept them as true. Actively open-minded thinking helps to distinguish between true and false. But the willingness to think deliberately does not seem to be important. (ii) By repeating false news stories, subjects are more likely to adequately identify them later (i.e., no evidence for a familiarity backfire effect). However, it decreased the ability to adequately identify correct news stories. A somewhat reverse, but weaker effect occurs when true stories are repeated: the correct identification of correct news stories is more successful, but the opposite holds for the identification of false news stories. Detailed explanations of why the false news stories contain false content increases the correct identification of false news stories, but the ability to correctly identify correct news stories is detrimental.
Keywords: C91; D91; Q50; 330; False news stories; narratives; cognitive reflection test; actively open-minded thinking; environmental economics; experimental economics